2013
DOI: 10.1242/jcs.121327
|View full text |Cite
|
Sign up to set email alerts
|

Amotl2 interacts with LL5β, localizes to podosomes and regulates postsynaptic differentiation in muscle

Abstract: SummaryNeuromuscular junctions (NMJs) in mammalian skeletal muscle undergo a postnatal topological transformation from a simple oval plaque to a complex branched structure. We previously showed that podosomes, actin-rich adhesive organelles, promote the remodeling process, and demonstrated a key role for one podosome component, LL5b. To further investigate molecular mechanisms of postsynaptic maturation, we purified LL5b-associated proteins from myotubes and showed that three regulators of the actin cytoskelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 74 publications
(109 reference statements)
2
60
0
Order By: Relevance
“…More recently, the actin nucleation factors neural Wiskott-Aldrich syndrome protein and actin related protein 2/3 have been implicated in agrin-induced AChR clustering (61). In addition, cluster maturation was associated with proteins like LL5␤, Paxillin, Vinculin and Talin (35,36). These proteins were also identified as regulated targets of MuSK signaling, uncovering a novel connection between agrin-induced phosphorylation and cytoskeletal dynamics during cluster development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the actin nucleation factors neural Wiskott-Aldrich syndrome protein and actin related protein 2/3 have been implicated in agrin-induced AChR clustering (61). In addition, cluster maturation was associated with proteins like LL5␤, Paxillin, Vinculin and Talin (35,36). These proteins were also identified as regulated targets of MuSK signaling, uncovering a novel connection between agrin-induced phosphorylation and cytoskeletal dynamics during cluster development.…”
Section: Discussionmentioning
confidence: 99%
“…Most prominently, Talin, Vinculin and Paxillin as components of synaptic podosomes at the site of AChR clusters (35,36); actin, F-actin and the actin binding protein MARCKS; and Myopaladin as an actincross-linking protein and cytoskeletal scaffolding protein (37,38) take part or assist in the network. Further, we detected a regulated phosphorylation for PDZRN3 (Cluster 2) and LL5␤ (Cluster 4), which have been functionally associated with AChR cluster formation (35,36,39). Our data now implicate phosphorylation as an important regulatory event during their cooperative action in the formation of AChR clusters.…”
Section: Agrin-induced Musk Stimulation and Ms Experimentalmentioning
confidence: 99%
“…CLASP and LL5-mediated anchoring of MTs to the basal cortex also plays a role during chicken embryonic development, where it prevents the epithelial-mesenchymal transition of epiblast cells (Nakaya et al, 2013). LL5b, CLASPs and ELKS were also shown to concentrate at podosomes, actin-rich structures, which can remodel the extracellular matrix (Proszynski and Sanes, 2013). Interestingly, LL5b-containing podosome-like structures are also formed at neuromuscular junctions (Kishi et al, 2005;Proszynski et al, 2009;Proszynski and Sanes, 2013), and the complexes of LL5b and CLASPs were shown to capture microtubule plus ends and promote delivery of acetylcholine receptors (Basu et al, 2015(Basu et al, , 2014Schmidt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…7A,B). As a positive control, we used an siRNA against MuSK, which we have previously shown blocks the formation of AChR clusters in this system (Proszynski and Sanes, 2013).…”
Section: α-Catulin Is Required For Achr Cluster Formationmentioning
confidence: 99%